Implementation of PAI Learning in Instilling Civilized Attitudes in Children Using Web Games - Mu'min, Khaerul; Kinzha Syakriani (Borneo Novelty Publishing, 2025)
Purpose—The use of technology in education is growing, and one of the latest innovations is the application of web games as a tool to teach mosque manners to children. This journal discusses the development and implementation of interactive web games specifically designed to introduce mosque adab values, such as politeness, order, and respect for places of worship. Through captivating and educational games, children can learn while playing, thereby increasing their motivation and interest in understanding mosque manners. Methodology/Design/Approach—This study uses a qualitative method to evaluate the effectiveness of web games in the learning process. Findings—The results showed that students showed an increase in understanding and application of mosque adab values after interacting with the game. In addition, web games also encourage social interaction among children, reinforcing a sense of community. Originality/value—These findings suggest that technology can be an effective tool in religious education and is expected to inspire educators to integrate innovative methods in learning mosque manners.